Qualitative properties of solutions of certain fourth order linear differential equations - W. E. Taylor (International Journal of Mathematics and Mathematical Sciences, 1981)
This work considers differential equations of the form (py″)′​′+qy″+ry=0 where p,q and r are positive continuous functions defined on [0,∞). The main concentration is on the oscillatory and asymptotic behavior of the solutions. Such an investigation is important because the above equation often arises in the study of mechanical vibrations.